Courses
Courses for Kids
Free study material
Offline Centres
More
Store Icon
Store

Theorems on Differentiation

ffImage
Last updated date: 23rd Apr 2024
Total views: 180k
Views today: 2.80k
hightlight icon
highlight icon
highlight icon
share icon
copy icon

A Brief Introduction to Differentiation Theorem

Theorems on differentiation specifically the sum, difference, product, and quotient rules are used in solving problems and finding the required solution. Here, we will discuss such fundamental theorems on differentiation with their detailed Proof. Differentiation is a fundamental tool of calculus and is also used as an alternative to the slope of the curve. In this article, we will learn and discuss some important theorems on differentiation. This will be followed by some solved examples for better understanding and clarity.


How to Define Differentiation?

Differentiation is defined as a derivative of a function with respect to an independent variable. Consider $y=f(x)$ be a function of $x$. Then, the rate of change of " $y$ " with respect to any change in " $x$ " is given as: $\dfrac{dy}{dx}$.


Mathematically,

$f(x)=\underset{h \rightarrow 0}{\lim}\dfrac{f(x+h)-f(x)}{h}$

Differentiation Graph


Differentiation Graph


History of Mathematician

There were many mathematicians associated with differentiation. However, the definition of differentiation was given by Issac Newton.

Isaac Newton, Image Credit: Wikimedia


Isaac Newton


Name: Isaac Newton

Born: 4 January 1643

Died: 31 March 1727

Field: Mathematics and Science

Nationality: England


Theorems and Proofs of Differentiation

1. Sum or Difference Rule

$\dfrac{d}{d x} f(x) \pm g(x)=\dfrac{d}{d x} f(x) \pm \dfrac{d}{d x} g(x)$\


2. Sum Rule

The derivative of the sum of two functions is the sum of the derivatives of the functions.

$\dfrac{d}{d x} f(x) \pm g(x)=\dfrac{d}{d x} f(x) \pm \dfrac{d}{d x} g(x)$


Proof:

By the definition of derivatives,

$\dfrac{d}{d x} f(x)+\dfrac{d}{d x} g(x)=\underset{h \rightarrow 0}{\lim} \dfrac{f(x+h)-f(x)}{h}+\underset{g \rightarrow 0}{\lim} \dfrac{g(x+h)-g(x)}{h}$

Take the RHS,

$\qquad R H S=\underset{h \rightarrow 0}{\lim} \dfrac{f(x+h)-f(x)+g(x+h)-g(x)}{h} \\ =\underset{h \rightarrow 0}{\lim} \dfrac{f(x+h)+g(x+h)-[f(x)+g(x))]}{h} \\ =\dfrac{d}{d x}[f(x)+g(x)] \\ =\text { LHS }$

Hence Proved.


3. Difference Rule

The derivative of the difference between two functions is the difference between the derivatives of the functions.

$\dfrac{d}{d x}[f(x)-g(x)]=\dfrac{d}{d x} f(x)-\dfrac{d}{d x} g(x)$


Proof:

By the definition of derivatives,

$\dfrac{d}{d x} f(x)-\dfrac{d}{d x} g(x)=\underset{h \rightarrow 0}{\lim} \dfrac{f(x+h)-f(x)}{h}-\underset{g \rightarrow 0}{\lim} \dfrac{g(x+h)-g(x)}{h}$

Take the RHS,

$R H S=\underset{h \rightarrow 0}{\lim} \dfrac{[f(x+h)-f(x)]-[g(x+h)-g(x)]}{h} \\ =\underset{h \rightarrow 0}{\lim} \dfrac{f(x+h)-g(x+h)-[f(x)-g(x))]}{h} \\=\underset{h \rightarrow 0}{\lim} \dfrac{f(x+h)-f(x)}{h}-\dfrac{g(x+h)-g(x)}{h} \\$

$=\dfrac{d}{d x}[f(x)-g(x)]$

$=$ LHS

Hence Proved.


4. Product Rule

The derivative of the product of two functions is given by the Product Rule.

$\dfrac{d}{d x}[f(x) g(x)]=\left[\dfrac{d}{d x} f(x)\right] g(x)+\left[\dfrac{d}{d x} g(x)\right] f(x)$


Proof:

By the definition of derivatives,

$\dfrac{d}{d x}[f(x) g(x)]=\underset{h \rightarrow 0}{\lim} \dfrac{f(x+h) g(x+h)-f(x) (g(x)}{h}$

By using the limit properties

$\underset{h \rightarrow 0}{\lim} f(x+h) \dfrac{g(x+h)-g(x)}{h}+\underset{h \rightarrow 0}{\lim} g(x) \dfrac{f(x+h)-f(x)}{h} \\\Longrightarrow\left[\underset{h \rightarrow 0}{\lim} f(x+h)\right] \left[\underset{h \rightarrow 0}{\lim} \dfrac{g(x+h)-g(x)}{h}\right]+\left[\underset{h \rightarrow 0}{\lim} g(x)\right] \\\left[\underset{h \rightarrow 0}{\lim} \dfrac{f(x+h)-f(x)}{h}\right] \\=\left[\dfrac{d}{d x} f(x)\right] g(x)+\left[\dfrac{d}{d x} g(x)\right] f(x)$

Hence Proved.


5. Quotient Rule

The derivative of the quotient of two functions is given by the Quotient Rule.

$\dfrac{d}{d x}=\dfrac{\left[\dfrac{d}{d x} f(x)\right] g(x)-\left[\dfrac{d}{d x} g(x)\right] f(x)}{g(x)^{2}}$


Proof:

By the definition of derivatives

$\underset{h \rightarrow 0}{\lim} \dfrac{\dfrac{f(x+h))}{g(x+h))}-\dfrac{f(x))}{g(x))}}{h}$

$\Rightarrow \underset{h \rightarrow 0}{\lim} \dfrac{1}{h} \dfrac{f(x+h) g(x)-f(x) g(x)+f(x) g(x)-f(x) g(x+h)}{g(x+h) g(x)} \\\Rightarrow \underset{h \rightarrow 0}{\lim} \dfrac{1}{g(x+h) g(x)} \\=\dfrac{f(x+h) g(x)-f(x) g(x)+f(x) g(x)-f(x) g(x+h)}{h} \\\Rightarrow\left[\underset{h \rightarrow 0}{\lim} \dfrac{1}{g(x+h) g(x)}\right] g(x) \dfrac{f(x+h)-f(x)}{h}-f(x) \dfrac{g(x+h)-g(x)}{h}$

By using the limit properties

$\Rightarrow \dfrac{1}{\underset{h \rightarrow 0}{\lim} g(x+h) g(x)} \left(\left[\left(\underset{h \rightarrow 0}{\lim} g(x)\right) \underset{h \rightarrow 0}{\lim} \dfrac{f(x+h)-f(x)}{h}\right]-\left[\left(\underset{h \rightarrow 0}{\lim} f(x)\right)\right.\right. \\\left.\left. \underset{h \rightarrow 0}{\lim} \dfrac{g(x+h)-g(x)}{h}\right]\right) \\\Rightarrow \dfrac{1}{g(x) g(x)}\left(g(x) f^{\prime}(x)-f(x) g^{\prime}(x)\right.$

$\Rightarrow \dfrac{f^{\prime} g-f g^{\prime}}{g^{2}}$

Hence Proved.


6. Constant Rule

The derivative of the constant functions is zero.

$\dfrac{d}{d x}(c)=0$


Proof:

Here $f(x)=c$, by the definition of the derivative, we have

$f^{\prime}(x)= \underset{h \rightarrow 0}{\lim} \dfrac{f(x+h)-f(x)}{h} \\ \Longrightarrow \underset{h \rightarrow 0}{\lim} \dfrac{c-c}{h} \\ \Longrightarrow \underset{h \rightarrow 0}{\lim} 0=0$


7. Power Rule

$\dfrac{d}{d x} x^{n}=n x^{n-1}$


Proof:

Assume $n$ to be a positive integer.

The binomial theorem states that

$(a+b)^{n}=a^{n}+n a^{n-1} b+\dfrac{n(n-1)}{2 !} a^{n-2} b^{2}+\cdots \ldots n a b^{n-1}+b^{n}$

where,

$\left(\begin{array}{l}k \\n\end{array}\right)=\dfrac{n !}{k !(n-k) !} \\n !=n(n-1)(n-2) \ldots . .(2)(1)$

From the definition of derivatives and using the binomial theorem

$\Rightarrow f^{\prime}(x)=\underset{h \rightarrow 0}{\lim} \dfrac{(x+h)^{n}-x^{n}}{h} \\\Rightarrow \underset{h \rightarrow 0}{\lim} \dfrac{x^{n}+n x^{n-1} h+\cdots \cdot}{h} \\\Rightarrow f^{\prime}(x)=\underset{h \rightarrow 0}{\lim} \dfrac{n x^{n-1}+\dfrac{n(n-1)}{2 !} x^{n-2} h^{2}+\cdots \ldots n x h^{n-1}+h^{n}}{h} \\\Rightarrow f^{\prime}(x)=\underset{h \rightarrow 0}{\lim} n x^{n-1}+\dfrac{n(n-1)}{2 !} x^{n-2} h+\cdots \ldots n x h^{n-2}+h^{n}-1 \\=n x^{n-1}$

Hence Proved.


8. Chain Rule

$\dfrac{d}{d x} f(u(x))=\left[f^{\prime} u(x)\right] \dfrac{d u}{d x}$


9. Rolle’s Theorem

Rolle's Theorem states that if $\mathrm{f}$ is a function that satisfies:

  1. $f$ is continuous on the closed interval $\left[a, b\right]$,

  2. $f$ is differentiable on the open interval $(a, b)$, and

  3. $f(a)=f(b)$

Then there exists a point $c$ in the open interval $(a, b)$ such that $f^{\prime}(c)=0$.


Solved Examples

1: Find $\dfrac{dy}{dx}$ of

$f(y)=\left(3 x^{3}-2 x^{2}\right)\left(4 x^{5}+x^{2}\right)$

Ans:

$\dfrac{d}{d x}\left(\left(3 x^{3}-2 x^{2}\right)\left(4 x^{5}+x^{2}\right)\right)$

Apply the Product Rule: $(f \cdot g)^{\prime}=f^{\prime} \cdot g+f \cdot g^{\prime}$

$\Rightarrow f=3 x^{3}-2 x^{2}, g=4 x^{5}+x^{2} \\\Longrightarrow \dfrac{d}{d x}\left(3 x^{3}-2 x^{2}\right)\left(4 x^{5}+x^{2}\right)+\dfrac{d}{d x}\left(4 x^{5}+x^{2}\right)\left(3 x^{3}-2 x^{2}\right)$

Apply the Sum/Difference Rule: $(f \pm g)^{\prime}=f^{\prime} \pm g^{\prime}$

$\Longrightarrow \dfrac{d}{d x}\left(3 x^{3}\right)-\dfrac{d}{d x}\left(2 x^{2}\right)$

$\Rightarrow \dfrac{d}{d x}\left(3 x^{3}\right)$


Apply the Power Rule: $\dfrac{d}{d x}\left(x^{a}\right)=a \cdot x^{a-1}$

$\Rightarrow 3 \cdot 3 x^{3-1}$

$\Longrightarrow 9 x^{2}$

$\Rightarrow \dfrac{d}{d x}\left(2 x^{2}\right)$

$\Rightarrow 2 \cdot 2 x^{2-1}$

$\Longrightarrow 4 x$


So,

$\Rightarrow \dfrac{d}{d x}\left(3 x^{3}\right)-\dfrac{d}{d x}\left(2 x^{2}\right) \\\Rightarrow 9 x^{2}-4 x \\\Rightarrow \dfrac{d}{d x}\left(4 x^{5}+x^{2}\right) \\\Rightarrow \dfrac{d}{d x}\left(4 x^{5}\right)+\dfrac{d}{d x}\left(x^{2}\right) \\\Rightarrow 20 x^{4}+2 x \\\Rightarrow\left(9 x^{2}-4 x\right)\left(4 x^{5}+x^{2}\right)+\left(20 x^{4}+2 x\right)\left(3 x^{3}-2 x^{2}\right) \\\Rightarrow 96 x^{7}-56 x^{6}+15 x^{4}-8 x^{3}$


2: In the mean value theorem, $f(b)-f(a)=(b-a) f^{\prime}(c)$ if $a=9, b=16$ and $f(x)=\sqrt{x}$ then what is the value of $c$ ?

Ans:

$F(x)=\sqrt{x}$

$\therefore f(a)=\sqrt{9}=3, f(b)=\sqrt{16}=4 ; f^{\prime}(x)=\dfrac{1}{2} \sqrt{x}$

Also, $f^{\prime}(c)=\dfrac{[f(b)-f(a)]} {[b-a]}=\dfrac{[4-3]}{16-9}=\dfrac{1}{7}$

$\therefore \dfrac{1}{2\sqrt{c}}=\dfrac{1}{7} \quad C=\dfrac{49}{4}=12.25$


Example 3: If the function $f(x)=x^{3}-6 x^{2}+a x+b$ satisfies Rolle's theorem in the interval $[1,3]$ and $f^{\prime}\left(\dfrac{2 \sqrt{3}+1}{\sqrt{3}}\right)=0$, then find the value of $a$.

Ans:

$f(x)=x^{3}-6 x^{2}+a x+b \\ \Rightarrow f^{\prime}(x)=3 x^{2}-12 x+a \\ \Rightarrow f^{\prime}(c)=0 \\ \Rightarrow f^{\prime}\left(2+\dfrac{1}{\sqrt{3}}\right)=0 \\ \Rightarrow 3(2+\sqrt{3})^{2}-12\left(2+\dfrac{1}{\sqrt{3}}\right)+a=0 \\ \Rightarrow 3\left(4+\dfrac{1}{3}+4 \sqrt{3}\right)-12\left(2+\dfrac{1}{\sqrt{3}}\right)+a=0 \\ \Rightarrow 12+1+4 \sqrt{3}-24-4 \sqrt{3}+a=0$

Now we get

$\Rightarrow a=11$


Conclusion

In this article, we have discussed the theorems on differentiation and their proofs. The proof, statement, and examples are thoroughly explained above. From the discussion above about the theorem on differentiation, we can conclude that they are very useful theorems to be used in solving calculus questions.


Important Differentiation Formulas to Remember

  • $\dfrac{d k}{d x}=0 \quad$ where $k=$ constant

  • $\dfrac{d(x)}{d x}=1$

  • $\dfrac{d(k x)}{d x}=k \quad$ where $k=$ constant

  • $\dfrac{d\left(x^{n}\right)}{d x}=n x^{n-1}$

Important Points to Remember

  • Concept of Differentiation, how to define differentiation must be studied in depth.

  • Differentiation is a synonym of slope.

Competitive Exams after 12th Science

FAQs on Theorems on Differentiation

1. Is every continuous function derivable and vice versa?

In calculus, it is not necessary that if a function is a continuous function, then it is derivable. But vice versa is true that if a function is derivable, it is obviously continuous. So, a continuous function may or may not be derivable while a derivable function is always continuous. For example, consider a function  $f(x)=|x|$ it is a continuous function but not derivable. So, a continuous function is not differentiable while every derivable function is continuous, which proves our point.

2. What is the difference between derivative and slope?

At a given point on a function, a derivative of a function is a study of the rate of change of one variable in relation to another variable. Whereas the slope is used to describe the steepness of a line which shows the relationship between the changes in y-values for a change in the value of x. In calculus, we use both these terms alternatively to find the slope of any curve. We find its derivative with respect to the independent variable which defines the curve.

3. What are the applications of derivatives in real life?

Derivatives have a wide range of applications in day to day life of every element on Earth. When a child is born, it grows with time. The rate of growth of a child with respect to time is calculated, which is a perfect example of a derivative. We use derivatives to find the maximum and minimum values of a function, to solve the displacement-motion problems, to find the acceleration given displacement or velocity, to find speed given distance at any time, and so on.